Peningkatan Motivasi dan Hasil Belajar IPAS dengan Model Project Based Learning di Sekolah Dasar - Khusnaeni, Nurul; Khusnaeni, Vera Yuli Erviana; Khusnaeni, Amiratun Solichah (Jurnal Didaktika Pendidikan Dasar, 2025)
The aim of this research is to determine the increase in motivation and learning outcomes through Project Based Learning with classroom action research that adopts the spiral model from Kemmis & McTaggart with two cycles. The data collection techniques used are tests and non-tests with observation and test techniques. The research subjects were 35 fifth grade students using qualitative and quantitative descriptive data analysis techniques. The research results showed that at the pre-cycle stage learning motivation reached 56% in the poor category, which increased to 62% in the sufficient category in cycle I, and reached 81.5% in the good category in cycle II. Meanwhile, learning outcomes at the pre-cycle stage were 11% in the very low category, which increased to 50% in the low category in cycle I, and reached 84% in the good category in cycle II. So it can be concluded that the application of the Project Based Learning model has increased the motivation and learning outcomes of class V students at SD Muhammadiyah Jogokariyan.